Estructura horizontal de especies comerciales del bosque de colina baja de la concesión forestal 16-MAY/C-D-002-14, distrito de Mazán, Loreto. 2021 - Brunner Rioja, Maria Fernanda (2022)
The horizontal structure of commercial species of the low-hill forest of forest concession 16-MAY/C-D-002-14, district of MazAn, Loreto, was determined. Data from the forest census of commercial species of PC1 for lumber purposes were evaluated. In total, 3870 trees, grouped into 38 forest species and 14 botanical families, were registered. The Fabacea family contains the highest number of species (eight species). The distribution of the number of trees by diameter class is 11,83 trees/ha (3870 trees), where V. mollissima (1,51 trees/ha, 494 trees), O. parvifolia (1,19 trees/ha, 389 trees), O. platyspermum (1,13 trees/ha, 371 trees), V. albidiflora (0,79 trees/ha, 257 trees) and S. amazonicum (0,72 trees, 237 trees) contain the highest number of trees. Ecologically, V. mollissima (Myristicaceae) is the most important with an IVI of 24,53%, followed by O. platyspermum (20,21%), O. parvifolia (19,97%), S. amazonicum (16,45%), V. albidiflora (15,92%), B. rubescens (13,77%), V. vismiifolia (13,05%), C. glabrum (13,05%), V. guianensis (12,88%) and A. brasiliensis (10,27%). The results show a highly significant difference between averages of the horizontal structure between species.